Identification of serotonin 5HT2receptors in bovine pineal gland - P. Govitrapong (2018)
Abstract: The concentration of serotonin in the pineal gland is extremely high, which prompted speculation that in addition to serving as a precursor of melatonin, serotonin may have an independent function of its own. By using [3H]‐spiperone as a ligand, and ketanserine as a selective serotonin 5HT2receptor antagonist, we have identified 5HT2receptor in the bovine pineal gland, revealing a single population of binding sites with a dissociation equilibrium constant (Kd) value of 1.26 ± 0.41 nM and a receptor density (Bmax) value of 193 ± 38.85 fmol/mg protein. In displacement experiments, the concentrations of the drugs required to inhibit 50% of the specific binding of [3H]‐spiperone in descending order of potency were methysergide > ritanserin > pirenperone > pipamperone > ketanserin > cyproheptadine > M‐trifluoromethylphenyl‐piperazine > prazosin > 5‐methoxy‐N‐N‐dimethyltryptamine hydrogen oxalate > 1‐(3‐chlorophenol) piperazine > serotonin. In the rat pineal gland, [3H]‐spiperone revealed a low affinity serotonin binding site with a Kd value of 25.77 ± 10.7 nM and a Bmaxvalue of 1244 ± 472 fmol/mg protein. The results of these studies are interpreted to indicate that the bovine pineal gland possess serotonin 5HT2receptor. However, the rat pineal gland possess a serotoninergic binding site of unknown nature. Copyright © 1991, Wiley Blackwell. All rights reserved